Independent Effects of Hypothyroidism and Obesity on Endometrial Cancer Risk Revealed by Mendelian Randomisation - Dylan M. Glubb; Xuemin Wang; Tracy A. O’Mara (Biomedicines, 2025)
Objectives: Thyroid dysfunction, particularly hypothyroidism, has been associated with endometrial cancer in observational studies; however, these findings may be confounded by obesity, an endometrial cancer risk factor. To clarify these associations, we performed Mendelian randomisation analysis, a genetic approach that mitigates confounding and reverse causation analyses. Methods: We accessed European-ancestry GWAS summary statistics for endometrial cancer (12,270 cases; 46,126 controls), endometrioid (8758 cases), and non-endometrioid (1230 cases) subtypes. Thyroid dysfunction phenotype and BMI GWAS data were predominantly from individuals of European descent. We used these datasets to conduct univariable and multivariable Mendelian randomisation analyses incorporating body mass index (BMI). Results: Our main finding was a causal association between hypothyroidism and decreased risk of endometrial cancer (OR = 0.93; 95% CI 0.89–0.97; p = 3.96 × 10−4). Subtype analysis revealed a decreased risk of the most common histological subtype, endometrioid endometrial cancer, and a similar protective association for Hashimoto’s thyroiditis, an autoimmune disease and common cause of hypothyroidism. Sensitivity analyses confirmed the robustness of the associations. Further analyses revealed that while BMI was causally associated with hypothyroidism risk, both BMI and hypothyroidism independently influenced endometrial cancer risk. Conclusions: Our study has identified hypothyroidism as a protective factor for endometrial cancer, challenging previous observational associations and highlighting potential confounding by obesity. Further investigation into immune mechanisms, particularly those linked to Hashimoto’s thyroiditis, may provide insights into the biological pathways underlying endometrial cancer development.